2014
DOI: 10.1123/jsep.2013-0038
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Multidimensional Model of Athletes’ Commitment to Coach-Athlete Relationships and Interdependent Sport Teams: A Substantive-Methodological Synergy

Abstract: Drawing from a three-factor model of organizational commitment, we sought to provide validity evidence for a multidimensional conceptualization designed to capture adolescent athletes’ commitment to their coach–athlete relationship or their team. In Study 1, 335 individual-sport athletes (Mage = 17.32, SD = 1.38) completed instruments assessing affective, normative, and continuance commitment to their relationship with their coach, and in Study 2, contextually modified instruments were administered to assess i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…To determine why some individuals remain in their organization despite showing signs of burnout and stating turnover intentions, there is a need to examine sport-related attitudes, such as commitment, identity, and engagement. Indeed, Jackson et al 56 found organizational commitment mediated attrition rates in adolescent groups in sport. In the same study, Jackson et al 56 developed a sport-specific measure of organizational commitment providing an excellent opportunity for future research to understand engagement, and intentions to turnover or actual turnover in sport organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine why some individuals remain in their organization despite showing signs of burnout and stating turnover intentions, there is a need to examine sport-related attitudes, such as commitment, identity, and engagement. Indeed, Jackson et al 56 found organizational commitment mediated attrition rates in adolescent groups in sport. In the same study, Jackson et al 56 developed a sport-specific measure of organizational commitment providing an excellent opportunity for future research to understand engagement, and intentions to turnover or actual turnover in sport organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Jackson et al 56 found organizational commitment mediated attrition rates in adolescent groups in sport. In the same study, Jackson et al 56 developed a sport-specific measure of organizational commitment providing an excellent opportunity for future research to understand engagement, and intentions to turnover or actual turnover in sport organizations. 2 The findings reported here suggest that emotional labor has significant explanatory potential for psychosocial dynamics and outcomes in sport, specifically, that surface acting is likely to lead to negative outcomes such as burnout and turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, established measures of behavioural regulations and psychological need satisfaction were adapted for the domain of walking behaviour and their hypothesised factor structures were tested using Bayesian structural equation modelling (BSEM; Muthén and Asparouhov, 2012). BSEM for the assessment of factorial validity is only just beginning to appear in the sport and exercise psychology literature (Barnett et al, in press;Gucciardi & Jackson, 2015;Gucciardi, Peeling, Ducker, & Dawson, 2014;Jackson, Gucciardi, & Dimmock, 2014;Stenling, Ivarsson, Johnson, & Lindwall, in press) but is not yet widely adopted.…”
Section: Basic Needs Theorymentioning
confidence: 99%
“…Bayesian analysis is an approach that has garnered the interests of sport and exercise psychology researchers in recent years (Doron & Gaudreau, 2014;Jackson, Gucciardi, & Dimmock, 2014). This approach leverages off theory and previous research to form a prior distribution -a combination of the specific magnitude and variability of effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian estimation has begun to garner the interests of researchers in the social sciences as a meaningful alternative to traditional methods (van de Schoot et al, 2014). By employing Bayesian estimation protocols in my thesis, I have contributed to the handful of other studies in sport psychology that have used these methods (e.g., Doron & Gaudreau, 2014;Jackson et al, 2014), and promoted the continued use of such approaches in the future. I share the opinion of some statisticians who believe that Bayesian estimation protocols will become the dominant statistical approach in the future (van de Schoot et al, 2014), as it services social science research better than traditional methods (e.g., null-hypothesis testing).…”
Section: Methodologicalmentioning
confidence: 99%